Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Tematik Terpadu dengan Model PBL di kelas V SD - Yanti, Rena Maiburni; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
AbtractThis research was backgrounded by unintegrated learning process applied to students in which a teacher, in this model of integrated thematic learning, had not introduced the students to actual cases happened in their environments. This research was aimed to describe the application of Problem Based Learning model to improve learning outcomes in integrated thematic learning to the students of grade V on SDN 114/III Dusun Baru Siulak Sungai Penuh Kerinci. The type of this research is CAR (Classroom Action Research) with mixed qualitative and quantitative approach. It was found in RPP that cycle I was 79.16% (C) in average, increased to 96.4% (SB) at cycle II. The implementation of learning on teacher aspect cycle I was 82.14% (B) in average and increased to 94.4% (SB) on cycle II. Meanwhile, the student aspect on cycle I was  82.14% (B) and increased to 94.4% (SB) on cycle II. The learning outcomes received on cycle I was 66.6% (D) in average and increased to 92.59% (SB) in average on cycle II